POLA PERILAKU KONSUMSI MAHASISWA BIDIKMISI 2013 (Studi tentang mahasiswa beasiswa bidikmisi 2013 Universitas Riau) - Sandra, Muhammad; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the relationship of income level of student bidikmisi against behavior patterns and to know the level of consumption behavior behavior of students bidikmisi 2013 Universitas riau. This research is a Quantitative research that is analyzed based on inferential statsitik. The theory used in this research is the theory of consumption society by Jean Baudrillard. In this research, there are 87 respondents. With technique sampling technique Sampling Propotional technique is used when the population has members who are not homogeneous stratified or not proportionately. The result of field obtained is the relation between income level of student of bidikmisi and consumption behavior pattern of student of bidikmisi, that is overall income level with consumption behavior pattern is Low, with result 0,229, based on qualification level relation. Overall Average Revenue Rate of student bidikmisi is is in the position of the interval to 2.98 or rounded 3. Position interval to 3 shows with the classification Medium with the ability of Student Revenue Rp.1000.001 - Rp.1.200.000 per month. Level of behavior pattern of student consumption with position of 2.51 lies on qualification interval coefficient 0,20 - 0,399 with Low level of relationship. And there is an indication of student bidikmisi 2013 Universitas Riau to behave consumptive although the relationship level of variable X and Y is low, Level of pattern of consumption behavior is low, and with income at interval 3 Rp. 1.000.001 - Rp.1.200.000 per month which can only to meet the priority needs, but in reality in the field not less when getting the accumulation of income that is from parent shipments, living board, and even business results.Keywords: Bidikmisi scholarships, students, consumption behavior